Effect of Incubation Period on the Physical Quality, pH, and Bulk Density of Fermented Rice Bran - Anggi Derma Tungga Dewi; Ririn Angriani (Universitas Veteran Bangun Nusantara, 2026)
This study evaluated the effect of incubation period on the physical quality of fermented rice bran prepared with an EM4-based starter under anaerobic conditions. Rice bran was assigned to four incubation periods, namely 0 day (P0), 7 days (P1), 14 days (P2), and 21 days (P3). The observed variables were color, aroma, texture, clumping tendency, insect-related visual score, pH, and bulk density. Incubation period modified several physical attributes of the material. Color scores decreased after fermentation, indicating a shift from brown to more yellowish-brown material, whereas aroma scores improved as incubation lengthened. Texture remained relatively unchanged across treatments. In contrast, the clumping score declined with longer incubation, showing a greater tendency of the product to form aggregates. The insect-related visual score also decreased after fermentation. The pH value declined progressively from the non-incubated treatment to the 21-day treatment, indicating increasing acidification during fermentation. Bulk density increased numerically up to 14 days and then slightly decreased at 21 days, although values remained higher than the control. Overall, incubation period was an important determinant of fermented rice bran quality. Longer incubation enhanced aroma and acid development, but it also altered color and increased clumping, indicating that incubation time should be selected according to the desired balance between sensory improvement and physical handling characteristics.